Analisis Teknik Penerjemahan Dari Tindak Tutur Memerintah Pada Film Elemental - Siti Fathiyatus Sholihah (Universitas Muhammadiyah Surabaya, 2026)
This study was conducted to determine governmental speech acts and specific techniques in translating them. This study can be classified as a qualitative descriptive study that focuses on one case. The data source for this study is the film Elemental and its Indonesian translation. Data were collected from statements containing commanding speech acts. From these data, the techniques applied to translate statements containing commanding speech acts were determined. There are two types of results, namely in the field of pragmatics and translation. In the field of pragmatics, there are 82 data on commanding speech acts. In addition, there are six types of translation techniques developed by Gottlieb (1992). The most frequently applied translation technique is deletion, which has 45 data (30%). Although deletion is the most common application, it does not affect the message conveyed because the audience can understand it from the visual images available on the screen.